An Italian experience of a new personalized injective protocol (Botutouch) for botulinum toxin application in aesthetic medicine. Issue 6 (27th October 2020) - Melfa, Fabrizio; Siragusa, Daniela; Caruso, Daniela Gaetana; Tunesi, Lucio; Zerbinati, Nicola; Chirico, Fabrizio; Lo Faro, Carmelo; Rauso, Raffaele
Abstract: Botulinum toxin typeA (BoNTA) is widely used in aesthetic medicine as primary treatment to reduce facial wrinkles. Major unmet needs in the field of the injection techniques include dilution factor, injected volume and site. Since 2013, an innovative protocol has been developed in our clinic that works on a double dilution volume, identifies the injection site according to the specific anatomical‐functional characteristics of each patient's musculature and applies a gentle massage to the injected area to optimize the toxin spread in the muscle. We retrospectively retrieved medical records of subjects that underwent aesthetic treatments in our outpatient Italian clinics from 2013. In cobotulinum toxin A was used in double dilution (100 AU in 5 mL of physiologic solution) and followed by a gentle massage after the injection to increase the distribution into the muscle. 197 subjects, most of them drug‐naïve (81.7%), underwent 869 BoNTA treatments. On average, higher total units and volumes were applied in first visits or older subjects whereas the lower ones were preferred in following visits or younger subjects. As perceived by the patients, the effects of BoNTA lasted more than 6 months in about 38% of the cases. 95.9% of subjects declared to be satisfied, whereas 5.2% of adverse events were observed (4.8% hematoma, 0.2% ptosis, and 0.2% tenderness). To date, we offer a BoNTA treatment with the aim to maximize the results and consequent patient's satisfaction, with low incidence of complications.